Besti (Stunting Free) Strategy Through Socialization of Fish Nutrition Education and Utilization of Yards for Green Vegetables in Maladummes Tanjung Kasuari Village, Sorong City - Ivonne M. Leiwakabessy; Dwi Indah Widya Yanti; Lili Sarce Joi Sapari; Hendrika Faubun; Novelia Gloria Molle (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
The stunting status in Southwest Papua has increased from 2021 to 2022. In 2021, stunting cases reached 26.3%, while in 2022 stunting cases rose 3.8% to 30%. Therefore, efforts to prevent, raise awareness and improve nutrition through increasing family income in the coastal areas of Sorong City need to be carried out. The implementation of stunting prevention outreach was carried out using a participatory approach, focused on discipleship cell groups (KSP), in RT.003/RW/004, Maladummes Tanjung Kasuari District, Sorong City. The aim of this activity is to increase parents' insight into choosing nutritious foods. The activities carried out were socialization of fish nutrition education, use of the yard for vegetable plants, knitting training, and continued provision of food. From the results of the knitting training, the participants felt that the training they received was very useful. Participants will make various types of knitting such as cellphone bags, handbags (various sizes), tablecloths and so on. These products will later be sold to increase family income.